Trends in selected birth defects among parents from below poverty line population in Karnataka during 2010-2020 - D C Nanjunda; S Jyothi Lakshmi; H Rajesh Acharya; Amit Kumar Mishra (Wolters Kluwer Medknow Publications, 2022)
The aim of the study is to reveal the common birth defects among parents of newborns belonging to the below poverty line (BPL) category in Karnataka state (South India) by analyzing Suvarna Arogya Suraksha Trust data. In the last 10 years, 3672 kids in BPL families have been born with various birth abnormalities. It is found that 50.3% of newborns have anorectal malformations, 33.1% have hypospadias, 6.0% have diaphragmatic hernia, 5.1% have esophageal atresia, and 2.8% have intestinal atresia and obstruct. As a parent's age rises, the likelihood of having a child with birth abnormalities raise as well, particularly anorectal malformations than diaphragmatic hernia. Male newborns have a higher risk of birth defects. We hypothesized that poverty, material deprivation, and low socioeconomic profile throughout the life course among the BPL community could be some of the key reasons for poor maternal health care and related neonatal outcomes.